Contando o passado, tecendo a saudade: a construção simbólica do engenho açucareiro em Jose Lins do Rego (1919-1943) - Freire, Diego José Fernandes (2014)
In this work I have searched the symbolical sense of a specific place. I have started from the theoretical assumption that places are social relations resulting from material and symbolical conditions developed in a certain time and by certain factors. In this sense, I have analyzed the symbolical aspect of sugar plantation from some literary works created by the writer José Lins do Rego from the state of Paraíba. I intend to analyze the symbolical dimension senses, values and images used by this writer to show the sugar plantation. Giving special attention to the works from the named cycle of sugar plantation , I have searched for the senses and meanings used in José Lins do Rego literary discourse to create a fictional sugar plantation, showing this place in a specific way. Based in cultural history, I have used several sources: literary works, prefaces of books, memory works, journalistic works, letters written by intellectual men and history books. My time of analysis is from 1919 the beginning of José Lins do Rego s intellectual activity - until 1943 publication of Fogo Morto, last literary work that I have analyzed. In symbolical terms, what is sugar plantation, this place that has totally touched José Lins do Regos life and literary work? That was the structural question that has determined the present research